The inter-relationship between work, education and human training: implications in teaching in professional education (Research, Society and Development, 2019)
The transformations which are processed in the labor market and the impact on the field of education emphasize the need to deepen the debate on this historical relationship. The critical reading of this scenario allows one to understand the new roles that education assumes as a strategic path coopted by capital. Thereby, the present article intends to discuss the relationship between work, education and human formation, situating the discussion around the implications that these interrelations causes in the whole society, with repercussions on the teaching work, especially in Professional Education. For the study we conducted literature and consulted authors such as Marx (2014), Braverman (1977), Antunes (2014), Kuenzer (2013), Ramos (2008, 2014), Moura (2014), among others. We start from the premise that the conjunctural scenario has caused significant changes for the labor category and for the working class. We pointed out that education is seen as a tool to solve the problem of employment and promote development by hiding the real interests of the hegemonic bloc.  Deepening the debate around the conception of human formation as a possibility to promote autonomy and emancipation in the subject. Finally, we highlight the nature of the work of the teacher and the possibility of assuming a working perspective counterhegemonic in the space of professional education.